The course of China's rural reform - Runsheng, Du (International Food Policy Research Institute, 2006)
For more than 20 years after the victory of the Chinese Revolution, radicalism was ascendant and private ownership of land was illegal. The peasantry became estranged from the land, so that when the Cultural Revolution ended, China’s economy had been placed in difficulty and an agricultural crisis induced. The population had grown, and food was in short supply. Per capita grain production never averaged much above 300 kilograms. Of the 800 million peasants, 250 million were impoverished. The nation as a whole could not achieve self-sufficiency in grain and required massive imports.